4z-6=-5+3z

Simple and best practice solution for 4z-6=-5+3z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4z-6=-5+3z equation:


Simplifying
4z + -6 = -5 + 3z

Reorder the terms:
-6 + 4z = -5 + 3z

Solving
-6 + 4z = -5 + 3z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-3z' to each side of the equation.
-6 + 4z + -3z = -5 + 3z + -3z

Combine like terms: 4z + -3z = 1z
-6 + 1z = -5 + 3z + -3z

Combine like terms: 3z + -3z = 0
-6 + 1z = -5 + 0
-6 + 1z = -5

Add '6' to each side of the equation.
-6 + 6 + 1z = -5 + 6

Combine like terms: -6 + 6 = 0
0 + 1z = -5 + 6
1z = -5 + 6

Combine like terms: -5 + 6 = 1
1z = 1

Divide each side by '1'.
z = 1

Simplifying
z = 1

See similar equations:

| 6-2(3x-3)+6x=15x-5(3x+2) | | 3x-x=-5 | | 3(3+6)=2(x+4) | | 6b-45=57 | | 3z-19=-35+5z | | 3(3+6)=2(9+4) | | 14+6g-5=40 | | 5y-27=3y+2 | | 6(7u-u)+u=36+u | | 3(4z-2)=2Z-36 | | 3+4z+9=31 | | 8(y+6)=128 | | 3(2x-5)+4(x+2)=-7 | | x^5-2x^4-8x^3=0 | | 2(x+4)=38-4x | | 6v+32=-6+8(v+4) | | -5/8=g-1/4 | | 0.6x=28.3 | | -6(4n-6)-2n=-7n+17 | | y-4=6 | | h+4/9=7/9 | | 7.4+d=-18.62 | | m-9.78=65.32 | | 6.3+k=12.5 | | b/4+10=13 | | 16+2a=-2(3a-4) | | 11-4x=6+x | | 4c+0=48 | | 3g-1+2g+8=g+2 | | A=5i+7j | | u+6=v | | -5+3x+3+2= |

Equations solver categories